2020
DOI: 10.26817/16925777.712
|View full text |Cite
|
Sign up to set email alerts
|

The Pre-Service EFL Teachers’ Development of Phonological Processing and Evaluation of Their Attitudes toward Pronunciation

Abstract: This study aimed at investigating EFL pre-service teachers’ attitudes toward pronunciation and pronunciation teaching. Another purpose was to explore the outcomes of pronunciation instruction on EFL pre-service teachers’ phonological development and based on the findings to provide suggestions taking learners’ pedagogical needs into consideration. The study was conducted using a quantitative research design method. 107 EFL pre-service teachers participated in the study. The quantitative instruments were Pronun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…That is, pre-and postintervention scores on oral presentation attributes are statistically significant. Similar research results by Aksakalli and Yağız [27], Gilakjani [37], and Kolokdaragh [38] revealed a substantial difference in comprehensibility and impact was due to phonological and phonetic awareness, and the significant difference between pretest and posttest ratings was defined as t (oral comprehensibility) = 13,555; p<0:05.…”
Section: Hypothesis Testingsupporting
confidence: 77%
See 1 more Smart Citation
“…That is, pre-and postintervention scores on oral presentation attributes are statistically significant. Similar research results by Aksakalli and Yağız [27], Gilakjani [37], and Kolokdaragh [38] revealed a substantial difference in comprehensibility and impact was due to phonological and phonetic awareness, and the significant difference between pretest and posttest ratings was defined as t (oral comprehensibility) = 13,555; p<0:05.…”
Section: Hypothesis Testingsupporting
confidence: 77%
“…The teachers must be proficient in varieties of English accents such as British and American English; the key is if the instructors are familiar with intelligible pronunciation [11]. An interventional study by Aksakalli and Yağız [27] revealed that "the participants in the study displayed significance in pronouncing phonemes. Further, this study revealed that participants had improved in both segmental and suprasegmental scores at the posttest."…”
Section: Literature Reviewmentioning
confidence: 99%